Point-of-Care Ultrasound Use to Differentiate Hematoma and Sarcoma of the Thigh in the Pediatric Emergency Department. Issue 2 (February 2017) - Le, Cathie-Kim; Harvey, Gregory; McLean, Lianne; Fischer, Jason
Abstract : Abstract: Hematomas and soft tissue sarcomas can be difficult to differentiate clinically, even with the addition of traditional imaging modalities. There are several case reports of sarcomas being misdiagnosed as hematomas, most commonly with a history of mild trauma. In this case report, we described a sarcoma initially misinterpreted as a hematoma on ultrasound. Key clinical features and sonographic findings that may assist clinicians using point-of-care ultrasound to correctly differentiate sarcomas from hematomas are reviewed. A soft tissue mass larger than 5 cm, with internal vascular Doppler flow, presenting without a clear mechanism of injury or with constitutional symptoms should be considered as suspicious for malignancy.